Effectiveness of combination theraphy of trigger point, deep tissue massage, and stretching for the low backpain healing - Nossanandi Krisnayantyo, Albertus Gracia; Graha, Ali Satia; Suhartini, Bernadetha; Noor, Mohad Anizu Mohd (Jurnal Keolahragaan, 2025)
This research aims to determine the effectiveness of the combination therapy of trigger point, deep tissue massage, and stretching towards the low back pain healing which is indicated by the decreasing pain and increasing flexibility. The research was conducted in December 2021 in Temanggung and Yogyakarta. This research was basically an experimental study. The research design utilized a pre-experimental design with a one group pretest posttest design. The research sample was for about 21 people with the characteristics of the subject of Non Specific Low Back Pain (NSLBP) acute and subacute phases. The sampling was done by utilizing the incidental sampling method. The instruments were VAS to measure pain and Fingertip to Floor (FTF) to measure lower back flexibility. The combination therapy treatment was done for about 50 minutes, started by the manipulation of trigger points in the deep spinal muscles, longisimus dorsi, iliocostalis, quadratus lumborum, gluteus, hamstring, soleus, psoas major, and quadriceps muscles, and continued with manipulation of deep tissue massage techniques in the area of back, hips, thighs, and calves, followed by stretching with active assisted stretching techniques such as the moves of cobra, childpose, cat and camel, thread the needle, gluteus stretch, and piriformis stretch. The data analysis technique utilized paired t test to determine the significance of the difference with the terms of significance of p < 0.05. The findings show that there is a difference between the pretest and the posttest. The results of this study indicate that in the pretest the average score of pain is at 77.48, ante flexion is at 10.81, dextro flexion at 35.21, and sinistro flexion at 34.95. After being given treatment, the average score of pain is at 32.14, ante-flexion at 4.31, 31.91, and sinistro flexion at 32.48. The results of the paired t test show a significance value of 0.000, subsequently it can be concluded that the combination therapy of trigger point, deep tissue massage, and stretching is effective for the low back pain healing with the effectiveness levels at 58.52%, 60.12%, 9.37%, and 7.06% respectively for pain reduction and increased flexibility of ante flexion, dextro flexion, and sinistro flexion.